PENGARUH PENGETAHUAN DAN EKSPEKTASI MASYARAKAT TERHADAP KESENJANGAN PERSEPSI AUDIT PEMERINTAHAN - Rizqi Ramadhony; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
Audit perception gap revealed a discrepancy between public perception as financial statements user and public auditor. People have a very broad perception of public auditor responsibilities. Public perception which influenced by various factors such as knowledge and expectations.This research aimed to examine whether or not there is a significant influence from public knowledge and expectation of public auditor duties and responsibilities on audit perception gap.Population in this research was public in general as users of financial statements with the sample were employees on public institutions and academics. This research was used purposive sampling and questionnaire was used as a method in collecting data, and then analyzed by using logistic regression.The results of this research shows that public knowledge of public auditor responsibilities as regulatory and professional bodies pronouncement and public expectation on public auditor to perform unreasonable responsibilities had significant influence on perception gap existence.